Paradigm-Independent Engineering of Complex Self-Organizing Systems - Zapf, Michael (Electronic Communications of the EASST, 2011)
We present EPAC, a novel approach to design and engineer systems of autonomous components. EPAC is based on the Model-Driven Architecture concept and subsumes concepts from different design paradigms that are related to the construction of complex systems, like multi-agent systems, multi-robot systems, or sensor networks. The design process introduces a generalized metamodel and starts at a high abstraction level which deﬁnes model elements for autonomous components, for structures, relationships, and behavior. We describe the stages of the modeling process, pointing out the speciﬁc differences to existing approaches.